PERTIMBANGAN HAKIM DALAM MENYELESAIKAN PERKARA CERAI GUGAT KARENA FAKTOR EKONOMI DALAM PERSPEKTIF HUKUM ISLAM (Studi Kasus Putusan Nomor 2721/Pdt.g/2023/PA.Jbg) - M. Widad Maulawy; Ahmad Ubaidi Hasbillah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. judge's thought in choosing a challenged separate case. The comes about of the investigate appear that cases of challenged separate by and large come from families with moo financial status, and the Board of Judges considers that the reason for nonstop debate and squabbles is the reason there's no trust of living in agreement within the family as expressed in article 19 of Government Direction No. 9 of 1975 which states applies in Indonesia. Divorce could be a claim for the proper to go to court (can be in composed or verbal frame) submitted by a spouse to separate from her spouse. The Offended party is the spouse who recorded for separate, and the Defendant is the spouse. Financial components can be a cause of separate since they can cause issues within the family, such as contentions, residential viciousness and treachery.